The Determinants Of Happiness: Empirical Evidence Of Java Island - Nandini, Dewi; Afiatno, Bambang Eko (Universitas Kadiri, 2020)
Happiness research on economics has increasingly developed since Easterlin Paradox appeared. This research tries to analyze the determinants of happiness in Java Island, Indonesia. We use data from the Happiness Measurement Survey 2017 conducted by the BPS-Statistic Agency of Indonesia. Taking 23,456 observations, we employ binary logistic regression to test the effects of 13 independent variables on happiness. The results showed that income, education, health, social relations with family and society, environmental conditions, and a meaningful life affect happiness. In general, these findings strengthen some previous studies findings.